Model Clustering Algoritma K-Mean Dalam Menentukan Kriteria Kondisi Gizi Balita Dan Anak - khairul zannah; Sumarno Sumarno; Zulaini Masruro Nasution; Iin Parlina; Ika Purnama Sari (Jurnal Dinamika Informatika, 2022)
The current level of health for toddlers and children is still a challenge in every region. Nutrition is very important for toddlers and children, a balanced nutritional value is very good in the process of growth and development of toddlers and children, especially in influencing height and weight growth, motor development, and daily activities. The problem currently being experienced in Nagori Sitalasari is that there are still many parents who do not know the value of balanced nutrition for toddlers and children, there are still toddlers and children who are still malnourished or stunted based on age and weight. The method used in this research is literature study and observation. This study will group or cluster the nutritional values of toddlers with reference to the parameters of toddler age, toddler height and toddler weight using the K-Means Clustering algorithm into 3 (three) categories, namely poor nutrition, good nutrition and obesity. The results of the research conducted can classify the nutritional value of children under five in general so that it can be used as a basis for early prevention for posyandu cadres to overcome malnutrition and obesity.